Let’s talk in coffee shop: 'maota di lapau' culture and declining trend - Chatra, Emeraldy; Thaufan, M; Zis, Sirajul Fuad (Jurnal Studi Komunikasi, 2025)
In West Sumatra, the Minangkabau community has a tradition known as Maota di Lapau (abbreviated as M.d.L), which involves conversational gatherings in coffee shops. However, this tradition is now eroding and being abandoned. The decline in the prestige of M.d.L has reduced the intensity of sharing thoughts and experiences, as well as creative and critical thinking. Furthermore, it has diminished the quality of social interaction and weakened the community's ability to unify its social potential to solve collective problems. This inductive research sought to provide a comprehensive explanation for why M.d.L is becoming less popular and declining in intensity, and to explore its implications for social capital, creativity, and the community's capacity for collaboration, particularly in the economic sphere. The study was conducted in four villages in West Sumatra using a qualitative method and a dual approach (case study and phenomenology). Analysis of the findings revealed that the primary cause is the discontinued use of the traditional communication protocol, Kato Nan Ampek, in daily conversation.